Electrocardiographic monitoring during marathon running: a proof of feasibility for a new telemedical approach. (29th August 2020) - Spethmann, Sebastian; Prescher, Sandra; Dreger, Henryk; Nettlau, Herbert; Baumann, Gert; Knebel, Fabian; Koehler, Friedrich
Abstract: Objective: There is a risk for sudden cardiac death and nonfatal arrhythmias for marathon runners. A new telemedical approach to prevent sudden cardiac death could be online electrocardiogram monitoring during endurance sport events, which would allow the emergency services located along the running track to initiate instantaneous therapy. In a first proof-of-concept study we evaluate the feasibility of recording, transferring and analysing an electrocardiogram via a mobile phone (electrocardiogram streaming) and compare the quality to a conventional Holter electrocardiogram during marathon running. Methods: A total of 10 recreational endurance runners are equipped with a Holter Tele-electrocardiogram and a standard smartphone connected via Bluetooth® to each other in order to continuously record an electrocardiogram during a first marathon event (five runners) and a second marathon event (five runners). All streaming electrocardiogram data were transferred from the device to our telemedicine centre (Charité Campus Mitte, Berlin, Germany); the data were monitored live and stored for a subsequent offline analysis. The primary endpoint was the percentage of successful transfer time of the streaming electrocardiogram compared with Holter electrocardiogram; the secondary endpoint was the percentage of correctly identified arrhythmias in the observed period. Results: It is technically feasible to stream an electrocardiogram during marathon running in the presence of thousands of mobile phone users. In addition, the identification of arrhythmias during a marathon is possible by electrocardiogram streaming. However, during the first race, the data transfer quality was low. After improvement of the software, in the subsequent race there was an extremely good quality in the data transfer via the mobile phone network (89%) and 100% of the rhythm disturbances could be detected in the streamed electrocardiogram. Conclusion: Online electrocardiogram surveillance during marathon running is a promising preventive concept. Intensive further technical development is needed first before further studies with clinical endpoints can start.